Diagnostic validity of the fifth edition of the Wechsler intelligence scales for children in characteristics Neuro-psychology of students with learning disability - Marzieh Shiri Aminlou; Parviz Sharifi Avaradi; Javad Khalatbari (مطالعات روانشناسی تربیتی)
This study was conducted with the aim of determining the diagnostic validity of the fifth edition of Wechsler's intelligence scales for children in the neuropsychological characteristics of students with learning disabilities in Tehran. The present study was subset of methodological studies. The number of 400 people with learning disabilities who were selected using a targeted and available sampling method and 400 normal people who were randomly selected from among all male and female students between the ages of 7 and 11 in Tehran in the academic year of 2018-2019. In line with the purpose of the research, the fifth edition of the Wechsler Children's Intelligence Scales (2014) was used. The collected data were analyzed using logistic regression analysis and SPSS software (Version 23).The study finally revealed that vocabulary and information tests (from verbal comprehension index), Block design with time point (from Visual-spatial index),arithmetic (from fluid reasoning scale), number span (direct), number span (reverse), picture span, letter-digit sequencing and letter-number sequencing (from working memory scale),and coding, cancellation (random), cancellation (structural), (from Processing speed index), had diagnostic validity.The fifth version of the Wechsler IQ Scales for children has diagnostic validity in the neuropsychological characteristics of students with learning disabilities and can distinguish students with learning disabilities from normal students.